Stanislav Dmytrovych Shevchenko - "ORTHOPAEDICS, TRAUMATOLOGY; PROSTHETICS", Staff of (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2023)
On April 21, 2020, an outstanding orthopedist-traumatologist, scientist and surgeon, a wonderful man, Doctor of Medical Sciences, Professor Stanislav Shevchenko passed away.